Sialotripsy as a treatment option for patients with salivary stone disease - A. V. Ivachenco; A. E. Yablokov; Е. О. Filatova; V. A. Monakov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2021)
Background. The pathologies of the salivary glands are very diverse. Salivary stone disease occupies a special place among diseases of the salivary glands of a non-neoplastic nature. The incidence of salivary stone disease is extremely extensive and accounts for up to 85% of all pathologies of the salivary glands.Objective. Improvement of minimally invasive methods of treatment of salivary stone disease, which does not lead to excision of the gland.Material and methods. On the basis of the Clinics of the Samara State Medical University of the Ministry of Health of Russia, in the period from 2010 to 2020, a clinical group was formed, consisting of 193 patients with salivary stone disease of various localization. The age of the patients ranged from 16 to 84 years. All patients were therapeutically examined at the preoperative stage, voluntary informed consent was signed. Shockwave sialotripsy was performed in 95 patients of the main group (in 64 patients the calculus was located in the submandibular salivary gland, in 31 patients – in the parotid salivary gland). For lithotripsy, we used a lithotripter apparatus "Edap" (France) and "Wolf" (Germany).Results. The analysis of the results obtained as a result of the study made it possible to draw a conclusion about reasonably better results of removal of calculi in the ducts of the salivary glands using the lithotripter "Swiss LithoClast® Master" (Switzerland). At the first visit and the therapeutic effect of the lithotripter, all patients suffering from bouts of salivary colic showed complete cessation.Conclusion. Thus our study, which was devoted to the study of the results of various methods of treating patients with salivary stone disease showed that sialolithotripsy using special narrowly targeted devices for crushing and subsequent excretion of salivary calculi allows to achieve the best results at present.